Economic empowerment through the development of food and beverage micro enterprises - Nurul Badriyah; Setyo Tri Wahyudi; Arum Prastiwi; Mokhamad Nur; Kartika Sari; Rihana Sofie Nabella; R. Radeetha (Universitas Muhammadiyah Malang, 2023)
Kecamatan Grati is one of the sub-districts in Pasuruan Regency, famous for its various potentials both in terms of tourism, religious areas and geographically strategic. This Community Service focuses on the food and beverage sector business belonging to LAZISNU (Lembaga Amil Zakat and Shodaqoh NU) in Kecamatan Grati, which is centered in the Pujasera MSME Center in Gratitunon Village. Another thing that also needs to be developed in this community group in Kecamatan Grati is the entrepreneurial spirit in order to produce a jointly managed business unit so that community empowerment in Kecamatan Grati can be ensured. Therefore, the service team carried out a mapping of problems related to improving the local economy faced by LAZISNU partners (business mamin) through FGDs, Technical Guidance about diversifivation product and socialization PIRT. The impact obtained by MSME actors on BIMTEK activities about diversification product are: (i) improved skills and knowledge (ii) increase in product added value (iii) expansion of market share (iv) increased competitiveness (v) improved brand image (vi) business continuity. Next, the impact obtained by MSME actors on BIMTEK activities about socialization PIRT are: (i) compliance with regulations (ii) product quality improvement (iii) customer trust (iv) access to a wider market (v) consumer protection (vi) increased professionalism. The originality of this service program (Pengabdian Kepada Masyarakat) is that MSME actors can increase their income, product diversification, and product added value, through technical guidance which is carried out by inviting speakers from the agricultural technology field.